Determination of Elastic Modulus of Thermoplastic Polymers with Pulse-Echo Method Ultrasonic Testing - - Nim: 13714025, Claudia
Polymers can be degraded by exposure to UV light and high humidity, resulted in decreasing the modulus of polymers which can lead to a structural failure. By monitor its modulus and predict the lifetime of polymer component, failure can be prevented. Non-destructive testing is preferred by industry for in-service monitoring of component, rather than destructive testing such as tensile tests which require component cutting. One of the nondestructive testing techniques is the ultrasonic technique. With ultrasonic technique, velocity of ultrasonic wave propagation passing through a material depends on the elasticity and material density. Velocity and attenuation difference can be utilized for testing the modulus of elasticity polymer due to degradation. There are two common ultrasonic methods. They are through transmission and pulse-echo. Pulse-echo is easier to use and require only one side of the material. This research aims to determine elastic modulus of thermoplastic polymers i.e. polymethylmethacrylate (acrylic), polyamide 6 (nylon) and low density polyethylene (LDPE). The study begins with determining and evaluating probes, namely probes with a diameter of 24 mm 1 MHz and 12.7 mm 1.5 MHz with and without additional probe delay. The probe evaluation result was the probe with a diameter of 12.7 mm 1.5 MHz with an additional delay probe was not be affected by nearfield for sample thickness above 14 mm. Then the elastic modulus of thermoplastic polymer through ultrasonic testing was determined according to the ASTM equation. The result were elastic modulus value obtained from ultrasonic velocity had a profound error 98% to 158%. Besides that the results show the thermoplastic polymerÃ‚Â’s attenuation was influenced by the viscoelastic properties of the polymer from DMA testing, density and affected the error of elastic modulus. The higher the viscoelastic property, the greater the attenuation and error. The lower the density, the greater the attenuation value and error. With the linear regression model, the elastic modulus of termoplastic polymer with pulse echo ultrasonic testing had a smaller error from 2.16% to 5.52%.